Nutritional Status and Menarche in Boarding School - Diana Diana; Is Susiloningtyas; Alfiah Rahmawati (JURNAL KEBIDANAN, 2021)
Nutritional status is one of the factors that can affects the reproductive system. In adolescence, nutritional status greatly influences the occurrence of menarche. This analysis aims to determine the relationship of nutritional status to the age of menarche in adolescents. This research was conducted at the Bunyanun Marshush Margoyoso Pati Boarding School. This type of researched is Analytic Cross Sectional Study. The subjects were 83 female students with the criteria of having experienced menarche. The independent variable studied was menarche age. The data analysis was performed using the Spearmann Rank Correlation. This study states that the majority of the nutritional status of female students is in the normal range (71.1%) compared to the abnormal range (28.9%). The variables related to nutritional status were menarche age with moderate correlation strength (r = 0.428). Nutritional status is related to the age of menarche. It is recommended for female students to reduce fast food or snacks to maintain a stable body weight. For Islamic boarding schools in order to be able to help students to meet nutritional intake every day by improving the quality of nutrition in accordance with balanced nutrition.